2004
DOI: 10.1038/ng1446
|View full text |Cite
|
Sign up to set email alerts
|

Cited2 controls left-right patterning and heart development through a Nodal-Pitx2c pathway

Abstract: Malformations of the septum, outflow tract and aortic arch are the most common congenital cardiovascular defects and occur in mice lacking Cited2, a transcriptional coactivator of TFAP2. Here we show that Cited2 -/-mice also develop laterality defects, including right isomerism, abnormal cardiac looping and hyposplenia, which are suppressed on a mixed genetic background. Cited2 -/-mice lack expression of the Nodal target genes Pitx2c, Nodal and Ebaf in the left lateral plate mesoderm, where they are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
196
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 44 publications
5
196
2
Order By: Relevance
“…Cited2 acts upstream of Nodal, a member of the TGF-␤ superfamily, and is required for normal establishment of the left-right axis (14,15). Overexpression of Cited2 in Rat1 cells results in loss of cell contact inhibition, anchorage-independent growth in soft agar, and tumor formation in nude mice, suggesting that Cited2 is a transforming gene (1).…”
Section: Cited2 (Camp-responsive Element-binding Protein-binding Protmentioning
confidence: 99%
“…Cited2 acts upstream of Nodal, a member of the TGF-␤ superfamily, and is required for normal establishment of the left-right axis (14,15). Overexpression of Cited2 in Rat1 cells results in loss of cell contact inhibition, anchorage-independent growth in soft agar, and tumor formation in nude mice, suggesting that Cited2 is a transforming gene (1).…”
Section: Cited2 (Camp-responsive Element-binding Protein-binding Protmentioning
confidence: 99%
“…Further studies revealed left-right patterning defects in these embryos, especially in co-isogenic C57BL/6J backgrounds (26). Moreover, CITED2 could selectively maintain adult hemopoietic stem cell functions, at least in part via Ink4a/Arf and Trp53 (27).…”
mentioning
confidence: 92%
“…2 These initial in vitro studies underscore the potential roles of Cited2 in different biologic processes. Deletion of Cited2 gene results in embryonic lethality in the mid to late gestation with embryos displaying cardiac malformations, neural tube defects, 7 adrenal agenesis, [8][9][10] left-right patterning defects, 9,11 and placental defects. 12 Further mechanistic studies have provided evidence that Cited2 plays pivotal roles in these processes through its transcriptional modulator functions for HIF-1 8,13 or AP-2␣ signaling.…”
Section: Introductionmentioning
confidence: 99%
“…12 Further mechanistic studies have provided evidence that Cited2 plays pivotal roles in these processes through its transcriptional modulator functions for HIF-1 8,13 or AP-2␣ signaling. [9][10][11] Accumulated evidence has implicated the role of Cited2 in hematopoiesis because Bmi-1, which is essential for adult hematopoietic stem cell self-renewal, 14 is induced by Cited2 in mouse embryonic fibroblast (MEF) cells. 15 CBP and p300 are fate decision factors for HSCs, responsible for HSC self-renewal and hematopoietic differentiation, respectively.…”
Section: Introductionmentioning
confidence: 99%